Schriftgelehrte Prophetie: der eschatologische Teufelsfall in Apc Joh 12 und seine Bedeutung für das Verständnis der Johannesoffenbarung - Dochhorn, Jan (Wissenschaftliche Untersuchungen zum Neuen Testament, 2010)
"Revelation 12 is a key text in the Apocalypse of John. Jan Dochhorn explains this pericope from the textual world in the Apocalypse of John and determines its significance for the book as a whole."--Publisher's web site